Game-Based Futsal Passing Training Model for Children Aged 10-12 Years - Darmawan Purba Bayangna; Oman Unju Subandi; Samsudin; Sujarwo (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Passing is a crucial aspect in futsal because it is the main key in building attacks and maintaining ball possession. This study aims to develop a game-based futsal passing training model for children aged 10-12 years. This study uses the Research and Development (RnD) method which refers to the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model involving 4 people as validators and 30 children as samples. Data collection was carried out through interviews, observations and tests. The results showed that 15 out of 23 were considered feasible and the model was able to improve futsal passing in children aged 10-12 years with a sig. value of 0.00 <0.05 which indicates a significant increase in the passing skills of children aged 10-12 years after being given the game-based passing training model treatment. The recommendations in this study are the importance of variation, active involvement, and contextualization in training.